PMSG-Based Black-Start Technology and Its Field Tests - Min-gang Tan; Yi Tang; Chaohai Zhang (Energies, 2019)
It is of great importance for power grids to have black-start capability for rapid recovery, and there is great theoretical significance and practical application value in studying how to use wind farms as the black-start power supply source for power grids with large-scale renewable energy generation. In this paper, a black-start scheme using a permanent-magnet synchronous generator (PMSG)-based wind farm as black-start power supply source is formulated. First, a diesel generator is used as an external supporting power supply for the self-start of a wind power unit (WPU). Then, after all the planned WPUs operate normally, the wind farm with the diesel generator and static var generator (SVG) is used to black start the simulated auxiliary load of a thermal power plant. A field test of the proposed black-start scheme is carried out on an actual wind farm in Jiangsu Province (China). The results of the field test show that wind farms can act as a black-start power supply source for the grid after appropriate technological transformation.